Draft Third Five Year Plan for the Laccadive Minicoy and Amindivi Islands - Planning Commission (Planning Commission, 1956)
The Union Territory of the Laccadive, Minicoy and Amindivi Islands was constituted with the reorganisation of States in November 1955. the inhabitants are all Scheduled Tribes An integrated five year plan was drawn up in 1957 after this Union Territory was constituted. Though it is termed as the 2nd five year plan of this Union Territory to correspond with the 2nd five year plan of the country, it was for all intents and purposes only its first five year plan; because the islands consisting this Union Territory were left untouched in the first five year plan of the country. Further, the 2nd five year plan covered only about 34 years as regards this Union Territory is concerned, as the plan was approved only towards the middle of 1957-58 and the actual execution started towards the end of that yearly. Expenditure sanctions of the Government of India had to be obtained for the execution of individual schemes.
Union Territory of Laccadive Minicoy and Amindivi Islands